Lead Exposure in Day Care Centers - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
The risk of lead poisoning among 155 of 234 eligible children (mean age, 4.8 years) enrolled in university affiliated day care centers with elevated environmental lead sources was determined at the Department of Pediatrics and University Hygienic Laboratory, The University of Iowa, Iowa City.